REVITALIZATION OF PANCASILA ETHICS AS MORAL BASIS IN THE LIFE OF NATION AND STATE - Ahmad Asroni (Sean Institute, 2023)
This article examines the revitalization of Pancasila ethics as the moral basis in the life of nation and state. The revitalization of Pancasila ethics is important and urgent to do because recently in Indonesia there has been a phenomenon of moral degradation among the community as well as violations of law and ethics such as corruption, bribery, radicalism, terrorism, and pornography carried out by state officials (executive, legislative, and judicative). Of course, these various violations of law and ethics, apart from having a bad impact on performance, also worsen the credibility and image of the institution. The state administration apparatus that should be a role model for the public slips into unlawful and commendable behavior. This article is conceptual research using the documentation method. The data is taken from various relevant and credible libraries/references. The results of this study are: First, the Pancasila Ethics is a moral philosophy or philosophy of morality based on the personality, ideology, soul, and way of life of the Indonesian people. Pancasila ethics are described from the Pancasila precepts to regulate the behavior of social life, nation, and state. In the ethics of Pancasila contained the values ​​of divinity, humanity, unity, democracy, and justice. Second, the revitalization of Pancasila ethics as the moral basis of society, nation, and state can be done in several ways, including: (1) Giving more portion to Pancasila ethical cultivation as the moral basis for society, nation, and state in the implementation of Pancasila Education and Civic Education in Indonesian educational institutions; (2) Increasing various trainings/workshops on the ethics of Pancasila as the moral basis of society, nation, and state for state apparatus; (3) Involving of religious and community leaders in inculcating the ethical values ​​of Pancasila.